Mobile photographic screening for dental caries in children: Diagnostic performance compared to unaided visual dental examination. (26th January 2021) - Estai, Mohamed; Kanagasingam, Yogesan; Mehdizadeh, Maryam; Vignarajan, Janardhan; Norman, Richard; Huang, Boyen; Spallek, Heiko; Irving, Michelle; Arora, Amit; Kruger, Estie; Tennant, Marc
Abstract: Objectives: This study was conducted to compare the use of intraoral photographs with the unaided visual dental examination as a means of dental caries detection in children. Methods: Children aged 4‐ to 14‐year‐olds were visually examined at their schools. Following dental examinations, children had five photographs of their teeth taken using a smartphone camera. Four dental reviewers, who are different from those who visually examined the children, assessed intraoral photographs for dental caries. Sensitivity, specificity, and inter‐rater reliability agreement were estimated to assess the diagnostic performance of the photographic method relative to the benchmark visual dental assessments. Caries prevalence was measured using dft/DFT (decayed and filled teeth) index. Results: One hundred thirty‐eight children (67 male and 71 female) were enrolled and had a mean age of 7.8 ± 2.1 years. The caries prevalence (dft/DFT > 0) using photographic dental assessments ranged from 30 percent to 39 percent but was not significantly different from the prevalence (42 percent) estimated with the visual dental examination ( P ≥ 0.07). The sensitivity and specificity of the photographic method for detection of dental caries compared to visual dental assessments were 58–80 percent and 99.7–99.9 percent, respectively. The sensitivity for the photographic assessments was high in the primary dentition (63–82 percent) and children ≤7‐year‐olds (67–78 percent). The inter‐rater reliability for the photographic assessment versus the benchmark ranged from substantial to almost perfect agreement (Kappa = 0.72–0.87). Conclusions: The photographic approach to dental screening, used within the framework of its limitations, yielded an acceptable diagnostic level of caries detection, particularly in younger children with primary dentition.